Professional development for the early learning content social studies standards - Laurie Katz; Hatice Zeynep İnan; Cynthia Tyson; Adrienne Dixson; Hyun-Young Kang (International Electronic Journal of Elementary Education, 2010)
This article describes early childhood educators’ responses to a professional development series aimed at helping them to understand and incorporate early learning standards for social studies. While the primary aim of the professional development was to focus on the social studies content standards, the secondary aim was to introduce early childhood educators to culturally relevant pedagogical strategies that take into account the unique learning needs of diverse children, particularly children of colour, English language learners and children with special needs. The findings suggest that early childhood educators can benefit from sustained professional development that not only addresses content standards but also helps them to understand how to incorporate the standards into their existing curriculum using developmentally and culturally appropriate pedagogy.